A quality health and physical education program making a difference for African American teenagers - Curren, Hattie Yvonne (Kansas State University, 2011)
A growing concern for the United States and the World Health Organization is that Americans are getting fatter. The obesity rates continue to rise in 23 states (Science & Technology, 2009). There is also a high incidence of childhood obesity among children ages 10-17. The epidemic of obesity goes far beyond being an individual problem. It has become a national crisis. The obesity epidemic calls for a well-formulated strategy. This study involved a physical education program with 12 African American female teenagers ranging from grades 7 – 11. The program was designed to help students realize the importance of preparing for a healthy future. The African American females met one hour a day for three days a week. As part of the program, each student’s fitness performance was evaluated using the FitnessGram protocol. Pretesting begins at the start of school and post testing during second semester. The FitnessGram report gives the performance levels for the Healthy Fitness Zone (HFZ) and the “Needs Improvement” zone. Attaining the HFZ for a test indicates that the student has a sufficient fitness level to provide important health benefits. The “Needs Improvement” zone indicates that the student may be at risk of health issues if that level of fitness remains the same over time. The Healthy Fitness Zone and Needs Improvement consists of three basic components: (1) Aerobic capacity; (2) muscle strength, endurance, and flexibility; (3) body composition (Meredith, FitnessGram, 2007). Students’ personal fitness information was charted daily during the program. The data collected for the personal profile assisted teenagers in setting goals related to reducing their weight and building self-esteem (Bronson, Glencoe Health, 2004). Monitoring and charting profiles provided guidelines for accomplishing goals that were necessary for changing students’ body image. The findings of this study indicated that the African American teenage participants did not want to commit to the exercise needed to improve their cardiovascular and personal fitness levels. Participants realized that skipping meals did not help with losing weight. When the students did eat, they tended to overeat and make unwise food choices.
Keywords: Physical Education; Obesity; Body Mass Index; Physical Activity; Overweight; FitnessGram; Healthy Fitness Zone; Education, Curriculum and Instruction (0727)